Human resilience and pain coping strategies: a review of the literature giving insights from elite ultra-endurance athletes for sports science, medicine and society - Paley, C. A.; Johnson, M. I. (Sports Medicine, 2025)
Background: Elite ultra-endurance athletes face extreme physical and psychological challenges, often enduring prolonged pain, fatigue and adverse environmental conditions. This article explores the pain coping strategies these athletes employ and highlights parallels with chronic pain populations. Through a combination of genetic predispositions, physiological conditioning and psychological resilience, ultra-endurance athletes tolerate prolonged and severe bodily pain and discomfort. Resilience and self-efficacy are crucial traits, allowing athletes to persist in extreme conditions. Adaptive coping strategies such as mindfulness, enhanced interoception and emotional regulation help athletes navigate pain whilst optimising performance. Methods and key findings: We searched five electronic databases for the literature on ultra-endurance activities and key psychological concepts, extracting significant themes. We draw on parallels between ultra-endurance athletes and individuals with chronic pain. Both groups benefit from similar coping mechanisms, including acceptance of pain, reinterpreting discomfort as a positive experience and using cognitive strategies. Ultra-endurance athletes, however, often reframe pain as part of the reward system associated with achievement, which differs from the distress-driven narrative of chronic pain populations. This allows athletes to achieve personal and competitive goals in the face of severe physical discomfort. We also explore the perceived locus of control and how this can drive a positive and reward-driven appraisal of bodily discomfort. Conclusions: Understanding the psychological processes and mental strategies that enable athletes to perform in such extreme conditions offers valuable insights into pain management and performance, emphasising the role of mental resilience, mindfulness and cognitive reappraisal. This demonstrates the potential for improving pain tolerance and mental well-being through adaptive mental strategies and focused training.